(untitled) - Donald J Conte (Dubuque, Iowa, 1993)
The book consists of 7 parts. Part 1, illustrates the holistic philosopy of earth science, identifies with the nature of scientific modeling, distinguishes between personal ans scientific information, justifies the necessity of using scientific instruments, distinguishes between the disciplines of earth science, recognizes and cites evidence for the practicality of earth science studies. Part 2 explains the origines universe and Solar System, compares the types and evolutionary stages of stars, generalizes from data teh nature of the planets and other celestial bodies. Part 3 describes the source of energy that drives atmospheres, identifies and cites evidence for the seasons, distinguishes the structures of atmospheres, classifies weather patterns, discusses the influence of weather on life. Part 4 inditifies the variable compositions of minerals and rocks, infers the distribution of elements in and on our planet, distinguishes the surface processes that shape the landscape, identifies and illustrate the internal processes that shape the planet's ocean basin and continents, recognizes how plate tectonic theory accounts for numerous geological phenomena. Part 5 relates the nature and signifiance of water, identifies and integrate the controls on seawater and its circulation, illustrates air-sea interactions, interpretes ocean environments and relationships to life. Part 6 distinguishes between renewable and nonrenewable resources, identifies the difficulties associated with discovering new sources of raw materials, claasifies soils, identifies the types and sources of metallic and nonmetallic resources, identifies the types and sources of fossil fuel resources. Part 7 indentifies the basic questions that led tto the development of earth history, distinguishes between absolute and relative age dating, classifies geologic time, relates Earth's early atmosphere to the rise of life, lists the major geologic events in the history of North America
Keywords: earth sciences